Insect sex chromosome evolution: Conservation, turnover, and mechanisms of dosage compensation - Toups, Melissa A; Vicoso, Beatriz (Current Opinion in Insect Science)
Sex chromosomes have evolved many times throughout the tree of life, and understanding what has shaped their unusual morphological, sequence, and regulatory features has been a long-standing goal. Most early insights into insect sex chromosome biology came from a few model species, such as the fruit fly Drosophila melanogaster, which limited broad-scale evolutionary inferences. More recently, extensive comparative genomics studies have uncovered several unexpected patterns, which we highlight in this review. First, we describe the conservation of the ancestral X chromosome over 450 million years but also its recurrent turnover (i.e. its reversal to an autosome when a new X chromosome arose) in at least one order. We then summarize classical and more recent findings on how insects modulate the expression of X-linked genes following the degradation of the Y chromosome and how the diverse mechanisms of dosage compensation identified may elucidate important principles of sex chromosome regulatory evolution.

Biosynthesis of very long-chain fatty acids is required for Arabidopsis auxin-mediated embryonic and post-embryonic development - Babic, David; Abualia, Rashed; Fiedler, Lukas; Qi, Linlin; Tellier, Frédérique; Smoljan, Adrijana; Rakusova, Hana; Valošek, Petr; Han, Huibin; Benková, Eva; Faure, Jean Denis; Friml, Jiří (Plant Journal)
Very long-chain fatty acids (VLCFAs), being constituents of different types of lipids, are critical factors in plant development, presumably due to their impact on the endomembrane system. The VLCFAs are synthesized in the endoplasmic reticulum by a heterotetrameric enzymatic complex including β-ketoacyl CoA reductase 1 (KCR1), whose mutant is lethal. Here, we describe the ectopic shoot meristems (esm) mutant, a viable kcr1 allele presumably affecting surface properties of the KCR1 protein. This kcr1-2 mutant shows reduced fatty acyl elongation that impacts VLCFAs. The kcr1-2 plants show severe defects during different stages of development, which all correlate with defects in polar localization and subcellular trafficking of PIN auxin transporters and resulting asymmetric auxin distribution. Detailed analysis of KCR1 expression and patterning defects in kcr1-2 suggests that KCR1 plays a role in delineating boundaries around meristematic and specialized differentiating tissues, including root and shoot meristems, initiating lateral roots, lateral root primordia, and trichomes. In these contexts, KCR1-produced VLCFAs may act in a non-cell-autonomous manner. Viable kcr1-2 represents a useful tool to study VLCFA roles in plant development and highlights VLCFAs as critical developmental factors at the interface of cell polarity and tissue development.

Amorphous high entropy alloy nanosheets enabling robust Li–S batteries - He, Ren; Lee, Seungho; Ding, Yang; Huang, Chen; Lu, Xuan; Zheng, Lirong; Yu, Ao; Zhang, Chaoyue; Li, Canhuang; Bi, Xiaoyu; Li, Yaqiang; Liao, Yaqi; et al. (Advanced Functional Materials)
High-entropy alloys (HEAs) show great potential for catalyzing complex multi-step reactions, but optimizing their parameters, i.e., composition, but also their crystallinity and morphology, remains a significant challenge. In this study, FeCoNiMoW HEAs are synthesized into either amorphous nanosheets (HEANS) or crystalline nanoparticles (HEANP), which are then used to catalyze the lithium–sulfur (Li–S) reaction of Li–S batteries (LSBs). Evaluations in symmetric cells, coin cells, and pouch cells reveal that HEANS significantly enhance LSB performance, achieving initial discharge capacities up to 1632 mAh g−1. The batteries also exhibit excellent cycling stability over 1000 cycles at 3Cand maintain high-rate performance up to 10C with a capacity of 614 mAh g−1. Comprehensive in situ analyses and density functional theory calculations demonstrate that amorphous HEANS provide more active sites, better ionic conductivity and stronger chemical interactions with lithium polysulfides (LiPS). These properties effectively suppress the shuttle effect, promote the complete S8 → Li2S conversion by reducing the impedance of the solid-electrolyte interphase, and accelerate the Li2S4 → Li2S2 step by lowering the nucleation energy barrier. Overall, this study highlights the superior catalytic properties of amorphous 2D HEAs in LSBs and offers new insights into the mechanisms of LiPS conversion.

Tribocharging of identical insulators : Triboelectric series, triboelectric cycles and surface charges - Sobarzo Ponce, Juan Carlos A
Tribocharging, or contact electrification, is the phenomenon in which two initially neutral materials exchange electric charge through contact and subsequent separation. While it is widely observed in everyday life and crucial to numerous natural processes, even the most basic aspects of tribocharging are still a mystery—what are the charge carriers involved and what drives their exchange? This work spans three separate projects that address different aspects of tribocharging. First, we introduce a novel strategy combining Finite Element Method (FEM) simulations with Kelvin Probe Force Microscopy (KPFM) to quantitatively extract surface charge density from surface voltage maps. Second, we present a simple theoretical model that allows for the existence of triboelectric cycles, under the assumption that multiple charge carrying species are involved. Third, we present experimental evidence that identical materials can spontaneously evolve into a triboelectric series, driven by contact history. Modeling this behavior enables the replication of experimental results with simulations, and even experimentally forcing the appearance of a pre-designed series by manipulating contact history. Together, the findings from these projects challenge traditional views on tribocharging, provide new tools for probing it, and open up new avenues of research—all with the hopes of bringing us closer to understanding this puzzling phenomenon.

Construction of a cryo-super-resolution microscope to guide in situ structure analysis - Vorlaufer, Jakob
The internal structure of biomolecules and their organization in higher-order arrangements are key factors governing the working principles of biological systems. Bioimaging has successfully revealed arrangements across relevant spatial scales. For example, cryo-electron tomography has become widely used for analyzing biomolecular structures in situ due to its comprehensive structural visualization of near-natively preserved samples, and its capability of sub-nm resolution via averaging. However, the identification of molecules within crowded cellular environments is often hindered by low contrast. Fluorescence microscopy, on the other hand, routinely visualizes specifically labeled targets at single-molecule contrast against essentially zero background. Moreover, it provides comparatively high throughput and is amenable to multiplexing. Due to this complementarity, combining datasets from both modalities acquired on the same region via correlative light and electron microscopy can reveal novel types of information. The spatial scale at which information can be extracted depends on imaging resolution and correlation accuracy. Since diffraction of light limits the resolution of conventional fluorescence microscopy to few hundreds of nanometers, reaching the full potential of correlative imaging requires super-resolution approaches. Performing imaging at cryogenic temperature preserves structures in a near-native state and minimizes distortions between the fluorescence and the electron microscopy datasets. Implementations of this concept have achieved correlation on the scale of cellular organelles or bacterial domains. We have worked towards pushing correlative imaging to the single-molecule scale by improving cryo-super-resolution microscopy, and devising a refined image correlation workflow. As part of this project, I constructed a microscopy setup and adopted it for super-resolution fluorescence microscopy at room temperature and cryogenic conditions. I explored different cryo-stages and acquisition strategies. Specifically, I developed a new scheme for correcting sample drift, thus increasing mechanical stability during microscopy acquisitions.

Unraveling the role of Pten in cortical stem cell lineage progression using MADM - Miranda, Osvaldo
Keywords: Pten; mtor; cortical development; MADM; Mapk

An extension of Muller's sheltering hypothesis for the evolution of sex chromosome gene content - Mrnjavac, Andrea; Vicoso, Beatriz; Connallon, Tim (Molecular Biology and Evolution)
The first influential hypothesis for sex chromosome evolution was proposed in 1914 by H. J. Muller, who argued that once recombination was suppressed between the X and Y chromosomes, Y-linked genes become “sheltered” from selection, leading to accumulation of recessive loss-of-function (LOF) mutations and decay of Y-linked genes. The hypothesis fell out of favor in the 1970s because early mathematical models failed to support it and data on the dominance of lethal mutations were viewed as incompatible with the hypothesis. We reevaluate the main arguments against Muller's hypothesis and find that they do not conclusively exclude a role for sheltering in sex chromosome evolution. By relaxing restrictive assumptions of earlier models, we show that sheltering promotes fixation of LOF mutations with sexually dimorphic fitness effects, resulting in decay of X-linked genes that are exclusively expressed by males and Y-linked genes that are primarily, though not necessarily exclusively, expressed by females. We further show that drift and other processes contributing to Y degeneration (i.e. selective interference and regulatory evolution) expand conditions of Y-linked gene loss by sheltering. The actual contribution of sheltering to sex chromosome evolution hinges upon the distribution of dominance and sex-specific fitness effects of LOF mutations, which we discuss.

Supermartingale certificates for quantitative omega-regular verification and control - Henzinger, Thomas A; Mallik, Kaushik; Sadeghi, Pouya; Zikelic, Dorde (37th International Conference on Computer Aided Verification)
We present the first supermartingale certificate for quantitative -regular properties of discrete-time infinite-state stochastic systems. Our certificate is defined on the product of the stochastic system and a limit-deterministic Büchi automaton that specifies the property of interest; hence we call it a limit-deterministic Büchi supermartingale (LDBSM). Previously known supermartingale certificates applied only to quantitative reachability, safety, or reach-avoid properties, and to qualitative (i.e., probability 1) -regular properties.We also present fully automated algorithms for the template-based synthesis of LDBSMs, for the case when the stochastic system dynamics and the controller can be represented in terms of polynomial inequalities. Our experiments demonstrate the ability of our method to solve verification and control tasks for stochastic systems that were beyond the reach of previous supermartingale-based approaches.

Robustness of solutions in game theory : Values and strategies in partially observable, perturbed, stochastic, and infinite games - Saona Urmeneta, Raimundo J
Game Theory is the mathematical formalization of social dynamics - systems where agents interact over time and the evolution of the state of the system depends on the decisions of every player. This thesis takes the perspective of a single player and focuses on what they can guarantee in the worst case over the behavior of other players. In other words, we consider that the objective of every other player in the game is exactly the opposite to the player. We focus on sustained interactions over time, where the players repeatedly obtain quantitative rewards over time, and they are interested in maximizing their long-term performance. Formally, this thesis focuses on zero-sum games with the liminf average objective. Two fundamental questions that Game Theory aims to answer are the following. 1. How much can a player guarantee to obtain after the interaction? 2. How to act in order to obtain the previously mentioned guarantee? These questions are formalized by the concepts of "value" and "optimal strategies". We study their properties on games that exhibit one or more of the following properties. 1. Partial Observation: the players can not perfectly observe the current state of the system during the game. We consider the model of (finite) Partially Observable Markov Decision Processes and prove that finite-memory strategies are sufficient to approximately guarantee the value. 2. Perturbed Description: the formal description of the game is perturbed by a small parameter. We consider the model of (finite) Perturbed Matrix Games, and provide algorithms to check various robustness properties and to compute the parameterized value and optimal strategies. 3. Stochastic Transitions: the actions of the players determine the behavior of the evolution of the system, described as a probability distribution over the next state. We consider the model of (finite) Perturbed Stochastic Games and provide formulas for the marginal value. 4. Infinite States: the system can be in infinitely many states. We consider the model of Random Dynamic Games on a class of infinite graphs, prove the existence of the value, and quantify the concentration of finite-horizon values.

Data of: "Quantifying the carbon footprint of conference travel: the case of NMR meetings" - Schanda, Paul
This repository contains calculations of carbon footprints of NMR conferences, as described in the article by Lucky N. Kapoor, Natalia Ruzickova, Predrag Živadinović, Valentin Leitner, Maria Anna Sisak, Cecelia Mweka, Jeroen Dobbelaere, Georgios Katsaros, and Paul Schanda Published in Magnetic Resonance, 2025.
Keywords: sustainability; conference travel

Integral points on cubic surfaces: heuristics and numerics - Browning, Timothy D; Wilsch, Florian Alexander (Selecta Mathematica New Series)
We develop a heuristic for the density of integer points on affine cubic surfaces. Our heuristic applies to smooth surfaces defined by cubic polynomials that are log K3, but it can also be adjusted to handle singular cubic surfaces. We compare our heuristic to Heath-Brown’s prediction for sums of three cubes, as well as to asymptotic formulae in the literature around Zagier’s work on the Markoff cubic surface, and work of Baragar and Umeda on further surfaces of Markoff-type. We also test our heuristic against numerical data for several families of cubic surfaces.

Stability estimate for the Lane–Emden inequality - Carlen, Eric; Lewin, Mathieu; Lieb, Elliott H.; Seiringer, Robert (Calculus of Variations and Partial Differential Equations)
The Lane–Emden inequality controls (math. formular) in terms of the L^1 and L^p norms of p. We provide a remainder estimate for this inequality in terms of a suitable distance of p to the manifold of optimizers.

Identification and elimination of surface emission in lanthanide (Co)doped zirconia nanocrystals - Reichholf, Nico; Horta, Sharona; Van Der Heggen, David; Seno, Carlotta; Pulparayil Mathew, Jikson; Ibáñez, Maria; Smet, Philippe F.; De Roo, Jonathan (ACS Nano)
Zirconia nanocrystals (ZrO2 NCs) are a stable host material for lanthanides, but their performance lags behind that of the leading NaYF4 nanomaterials. Here, we leverage surface chemistry and core/shell architectures to uncover the contribution of dopants at the nanocrystal surface and of dopants in the nanocrystal bulk. We first assess the doping efficiency by ICP and find that, while Eu is almost quantitatively incorporated, the other lanthanides (La, Ce, Tb, Tm, Er, Yb) have about 50% incorporation efficiency over the studied doping range of 1–10%. We then determine the nanocrystal surface chemistry using NMR spectroscopy, despite the additional spectral line broadening caused by the paramagnetic lanthanide dopants. By varying the surface ligands and measuring the photoluminescence, we resolve the spectroscopic signals that are sensitive to a change in surface chemistry. Time-resolved emission spectra further reinforce the notion of a bulk component with a long luminescent lifetime and a surface component with a fast lifetime. Upon shelling Eu- or Tb-doped zirconia NCs with pure zirconia, the surface component disappears, and the photoluminescence quantum yield increases. We further functionalized the surface of the core/shell particles with oleylphosphonic acid ligands to obtain excellent dispersibility. These results show that lanthanide-doped zirconia NCs can be engineered to eliminate deactivation pathways.

Quantitative language automata - Henzinger, Thomas A; Kebis, Pavol; Mazzocchi, Nicolas Adrien; Sarac, Naci E (36th International Conference on Concurrency Theory)
A quantitative word automaton (QWA) defines a function from infinite words to values. For example, every infinite run of a limit-average QWA 𝒜 obtains a mean payoff, and every word w ∈ Σ^ω is assigned the maximal mean payoff obtained by nondeterministic runs of 𝒜 over w. We introduce quantitative language automata (QLAs) that define functions from language generators (i.e., implementations) to values, where a language generator can be nonprobabilistic, defining a set of infinite words, or probabilistic, defining a probability measure over infinite words. A QLA consists of a QWA and an aggregator function. For example, given a QWA 𝒜, the infimum aggregator maps each language L ⊆ Σ^ω to the greatest lower bound assigned by 𝒜 to any word in L. For boolean value sets, QWAs define boolean properties of traces, and QLAs define boolean properties of sets of traces, i.e., hyperproperties. For more general value sets, QLAs serve as a specification language for a generalization of hyperproperties, called quantitative hyperproperties. A nonprobabilistic (resp. probabilistic) quantitative hyperproperty assigns a value to each set (resp. distribution) G of traces, e.g., the minimal (resp. expected) average response time exhibited by the traces in G. We give several examples of quantitative hyperproperties and investigate three paradigmatic problems for QLAs: evaluation, nonemptiness, and universality. In the evaluation problem, given a QLA 𝔸 and an implementation G, we ask for the value that 𝔸 assigns to G. In the nonemptiness (resp. universality) problem, given a QLA 𝔸 and a value k, we ask whether 𝔸 assigns at least k to some (resp. every) language. We provide a comprehensive picture of decidability for these problems for QLAs with common aggregators as well as their restrictions to ω-regular languages and trace distributions generated by finite-state Markov chains.

Maintaining diversity in structured populations - Brewster, David A.; Svoboda, Jakub; Roscow, Dylan; Chatterjee, Krishnendu; Tkadlec, Josef; Nowak, Martin A. (PNAS Nexus)
We examine population structures for their ability to maintain diversity in neutral evolution. We use the general framework of evolutionary graph theory and consider birth–death (bd) and death–birth (db) updating. The population is of size N. Initially all individuals represent different types. The basic question is: what is the time TN until one type takes over the population? This time is known as consensus time in computer science and as total coalescent time in evolutionary biology. For the complete graph, it is known that TN is quadratic in N for db and bd. For the cycle, we prove that TN is cubic in N for db and bd. For the star, we prove that TN is cubic for bd and quasilinear (N log N) for db. For the double star, we show that TN is quartic for bd. We derive upper and lower bounds for all undirected graphs for bd and db. We also show the Pareto front of graphs (of size N = 8) that maintain diversity the longest for bd and db. Further, we show that some graphs that quickly homogenize can maintain high levels of diversity longer than graphs that slowly homogenize. For directed graphs, we give simple contracting star-like structures that have superexponential time scales for maintaining diversity.

Predictive monitoring of black-box dynamical systems - Henzinger, Thomas A; Kresse, Fabian; Mallik, Kaushik; Yu, Zhengqi; Zikelic, Dorde (7th Annual Learning for Dynamics & Control Conference)
We study the problem of predictive runtime monitoring of black-box dynamical systems with quantitative safety properties. The black-box setting stipulates that the exact semantics of the dynamical system and the controller are unknown, and that we are only able to observe the state of the controlled (aka, closed-loop) system at finitely many time points. We present a novel framework for predicting future states of the system based on the states observed in the past. The numbers of past states and of predicted future states are parameters provided by the user. Our method is based on a combination of Taylor’s expansion and the backward difference operator for numerical differentiation. We also derive an upper bound on the prediction error under the assumption that the system dynamics and the controller are smooth. The predicted states are then used to predict safety violations ahead in time. Our experiments demonstrate practical applicability of our method for complex black-box systems, showing that it is computationally lightweight and yet significantly more accurate than the state-of-the-art predictive safety monitoring techniques.

Burning or collapsing the medial axis is unstable - Chambers, Erin Wolf; Fillmore, Christopher D; Stephenson, Elizabeth R; Wintraecken, Mathijs (La Matematica)
The medial axis of a set consists of the points in the ambient space without a unique closest point in the original set. Since its introduction, the medial axis has been used extensively in many applications as a method of computing a skeleton topologically equivalent to the original set. Unfortunately, one limiting factor in the use of the medial axis of a smooth manifold is that it is not necessarily topologically stable under small perturbations of the manifold. To counter these instabilities, various prunings of the medial axis have been proposed in the computational geometry community. Here, we examine one type of pruning, called burning. Because of the good experimental results it was hoped that the burning method of simplifying the medial axis would be stable. In this work, we show a simple example that dashes such hopes. Based on Bing’s house with two rooms, we demonstrate an isotopy of a shape where the medial axis goes from collapsible to non-collapsible. More precisely, we consider the standard deformation retract from the closed ball to Bing’s house with two rooms, but stop just short of the point where Bing’s house becomes two dimensional. This way we obtain an isotopy from the 3-ball to a thickened version of Bing’s house. Under this isotopy, the medial axis goes from collapsible to non-collapsible. We stress that this isotopy can be made generic, in the sense of singularity theory, as developed by Arnol’d and Thom.

Design and control of deformable structures: From PCB lighting displays to elastomer robots - Bhargava, Manas
Complex 3D shapes can be created by morphing flat 2D configurations. Such deformations either preserve the intrinsic material geometry (e.g., folding paper) or modify it through localized contraction. Once transformed, the 3D shape can be further controlled to achieve a target functionality. A key challenge is to take the material specifications and the actuation process as input to automatically design the target 3D shape and its functionality. This thesis presents two novel computational pipelines for the design and control of shape-morphing structures used to create functional prototypes. The first pipeline borrows from the art of origami to fold paper into intricate shapes and applies this principle to make 3D lighting displays. We introduce, PCBend a computational design approach that covers a surface with individually addressable RGB LEDs, effectively forming a low-resolution surface by folding rigid printed circuit boards (PCBs). We optimize cut patterns on PCBs to act as hinges and co-design LED placement, circuit routing, and fabrication constraints to produce PCB blueprints. The PCBs are fabricated using automated standard manufacturing services with LEDs embedded on them. Finally, the fabricated PCBs are cut along the contour and folded onto a 3D-printed support. The 3D lighting display is then controlled to display complex surface light patterns. Creating 3D shapes through folding is only possible if their planar configuration, called ”unfolding” exists without any distortion or overlap. Existing methods often permit distortion or require multiple patches, which are unsuitable for fabrication pipelines that rely on folding non-stretchable materials. We reinforce such fabrication pipelines by providing a geometric relaxation to the problem, where the input shape is modified to admit overlap-free unfolding. The second fabrication pipeline extends shape morphing to soft robotics by emulating nature’s blueprint of distributed actuation. Inspired by vertebrates, we build musculoskeletal robots using modular active actuators, employing Liquid Crystal Elastomers (LCEs) as shrinkable artificial muscles integrated with 3D-printed bones. The chemical composition of LCEs is altered to enable untethered actuation through infrared radiation, allowing active control of individual muscles and their corresponding bones. The combined motion of individual bones defines the robot’s overall shape and functionality. Our proposed system significantly expands both the design and control spaces of soft robots, which we harness using our computational design tools. We build several physical robots that exhibit complex shape morphing and varied terrain navigation, showcasing the versatility of our pipeline. This thesis explores applications ranging from intricate light patterns displayed on 3D shapes formed by folding rigid PCBs to untethered robots that use contractile muscles to exhibit shape morphing and locomotion. Through these examples, the thesis highlights how computational design and distributed actuation, integrated with novel materials, can transform passive structures into functional prototypes.

Computational design and fabrication of modular robots with untethered control - Bhargava, Manas; Hiraki, Takefumi; Strugaru, Irina-Malina; Zhang, Yuhan; Piovarci, Michael; Daraio, Chiara; Iwai, Daisuke; Bickel, Bernd (arXiv)
Natural organisms utilize distributed actuation through their musculoskeletal systems to adapt their gait for traversing diverse terrains or to morph their bodies for varied tasks. A longstanding challenge in robotics is to emulate this capability of natural organisms, which has motivated the development of numerous soft robotic systems. However, such systems are generally optimized for a single functionality, lack the ability to change form or function on demand, or remain tethered to bulky control systems. To address these limitations, we present a framework for designing and controlling robots that utilize distributed actuation. We propose a novel building block that integrates 3D-printed bones with liquid crystal elastomer (LCE) muscles as lightweight actuators, enabling the modular assembly of musculoskeletal robots. We developed LCE rods that contract in response to infrared radiation, thereby providing localized, untethered control over the distributed skeletal network and producing global deformations of the robot. To fully capitalize on the extensive design space, we introduce two computational tools: one for optimizing the robot's skeletal graph to achieve multiple target deformations, and another for co-optimizing skeletal designs and control gaits to realize desired locomotion. We validate our framework by constructing several robots that demonstrate complex shape morphing, diverse control schemes, and environmental adaptability. Our system integrates advances in modular material building, untethered and distributed control, and computational design to introduce a new generation of robots that brings us closer to the capabilities of living organisms.

Self-generated chemotaxis of mixed cell populations - Ucar, Mehmet C; Zane, Alsberga; Alanko, Jonna H; Sixt, Michael K; Hannezo, Edouard B (Proceedings of the National Academy of Sciences)
Cell and tissue movement in development, cancer invasion, and immune response relies on chemical or mechanical guidance cues. In many systems, this behavior is locally directed by self-generated signaling gradients rather than long-range, prepatterned cues. However, how heterogeneous mixtures of cells interact nonreciprocally and navigate through self-generated gradients remains largely unexplored. Here, we introduce a theoretical framework for the self-organized chemotaxis of heterogeneous cell populations. We find that the relative chemotactic sensitivities of different cell populations control their long-time coupling and comigration dynamics, with boundary conditions such as external cell and attractant reservoirs substantially influencing the migration patterns. Our model predicts an optimal parameter regime that enables robust and colocalized migration. We test our theoretical predictions with in vitro experiments demonstrating the comigration of distinct immune cell populations, and quantitatively reproduce observed migration patterns under wild-type and perturbed conditions. Interestingly, immune cell comigration occurs close to the predicted optimal regime. Finally, we incorporate mechanical interactions into our framework, revealing a nontrivial interplay between chemotactic and mechanical nonreciprocity in driving collective migration. Together, our findings suggest that self-generated chemotaxis is a robust strategy for the navigation of mixed cell populations.